Hepatic encephalopathy is not a contraindication to pre-emptive TIPS in high-risk patients with cirrhosis with variceal bleeding. Issue 4 (9th September 2022) - Rudler, Marika; Hernández-Gea, Virginia; Procopet, Bogdan Dumitru; Giráldez, Alvaro; Amitrano, Lucio; Villanueva, Càndid; Ibañez, Luis; Silva-Junior, Gilberto; Genesca, Joan; Bureau, Christophe; Trebicka, Jonel; Bañares, Rafael; et al.
Abstract : Background: A pre-emptive transjugular intrahepatic portosystemic shunt (pTIPS) reduces mortality in high-risk patients with cirrhosis (Child-Pugh C/B+active bleeding) with acute variceal bleeding (AVB). Real-life studies point out that <15% of patients eligible for pTIPS ultimately undergo transjugular intrahepatic portosystemic shunt (TIPS) due to concerns about hepatic encephalopathy (HE). The outcome of patients undergoing pTIPS with HE is unknown. We aimed to (1) assess the prevalence of HE in patients with AVB; (2) evaluate the outcome of patients presenting HE at admission after pTIPS; and (3) determine if HE at admission is a risk factor for death and post-TIPS HE. Patients and methods: This is an observational study including 2138 patients from 34 centres between October 2011 and May 2015. Placement of pTIPS was based on individual centre policy. Patients were followed up to 1 year, death or liver transplantation. Results: 671 of 2138 patients were considered at high risk, 66 received pTIPS and 605 endoscopic+drug treatment. At admission, HE was significantly more frequent in high-risk than in low-risk patients (39.2% vs 10.6%, p<0.001). In high-risk patients with HE at admission, pTIPS was associated with a lower 1-year mortality than endoscopic+drug (HR 0.374, 95% CI 0.166 to 0.845, p=0.0181). The incidence of HE was not different between patients treated with pTIPS and endoscopic+drug (38.2% vs 38.7%, p=0.9721), even in patients with HE at admission (56.4% vs 58.7%, p=0.4594). Age >56, shock, Model for End-Stage Liver Disease score >15, endoscopic+drug treatment and HE at admission were independent factors of death in high-risk patients. Conclusion: pTIPS is associated with better survival than endoscopic treatment in high-risk patients with cirrhosis with variceal bleeding displaying HE at admission.